Enkele etiese aspekte van natuurbewaring - Engelbrecht, B. J. (Hervormde teologiese studies, 1992)
Certain ethical aspects of nature conservation The present worldwide ecocrisis is of such a magnitude and seriousness that man’s life, living standards, future and very existence on earth are at stake. The main components of this man-made ecocrisis are the existing increasing overpopulation of earth, the exorbitant demands on the natural resources of our planet, the pace at which the non-renewable energy and other resources are being depleted and the pollution of the whole earth. In this paper we shall treat the population explosion problem as perhaps the most basic of the four components of the ecocrisis; we shall also give special attention to the associated ethical issues.